Genetic diversity of Aspergillus flavus and occurrence of aflatoxin contamination in stored maize across three agro-ecological zones in Kenya - Gachara, G.W.; Nyamache, A.K.; Harvey, Jagger J.W.; Gnonlonfin, G.J.B.; Wainaina, James (Springer, 2018)
Aflatoxin contamination at pre- and post-harvest poses a serious challenge in achieving sustainable development goals on food security and food safety, in particular within the developing world. In Kenya, major outbreaks of aflatoxicoses have been reported and attributed to poor post-harvest storage practices. In this study, we conducted a cross-sectional survey within three Agro-ecological zones in Kenya, to determine occurrence and distribution of total aflatoxin in stored maize and the aflatoxigenicity potential of Aspergillus flavus in stored maize. The counties selected were: Kitui, Nakuru and Trans-Nzoia. Sampling sites were selected based on previous aflatoxicoses outbreaks (Kitui) and major maize production areas (Nakuru and Trans-Nzoia) where little information exists on the occurrence of aflatoxin contamination. One hundred and thirty (130) kernel maize samples were randomly collected. Aspergillus flavus was isolated by direct plating technique. Genetic diversity of the isolates was determined by PCR and single sequence repeats (SSR) microsatellites analysis. Positive strains were induced to produce B1 aflatoxins on yeast extract sucrose agar and quantified using competitive ELISA technique. Total aflatoxin contamination of post-harvest stored maize samples between sites was significantly different (p = 0.000, < 0.05), with the highest contamination in Kitale at a mean of (9.68 µg/kg). A. flavus was isolated in 70% (N = 91) of the maize samples collected at post-harvest. A. flavus isolates with the highest aflatoxigenicity potential were from Nakuru County with mean aflatoxin level at 239.7 µg/kg. Genetic distance based on neighbor joining (NJ) clustered the A. flavus isolates into five main clusters including one clade with an admixture. Principal coordinate analysis showed five distinct clusters with both axes explaining 60.17% of the variance. This study showed widespread distribution of aflatoxin contamination and a highly toxigenic A. flavus in stored maize in three major agro-ecological zones in Kenya. These results suggest a potential health risk of aflatoxin outbreaks under favorable conditions within these areas, thus calling for more investigations.